Batch assays for biological sulfate-reduction: a review towards a standardized protocol. Issue 12 (17th June 2020) - Serrano, Antonio; Peces, Miriam; Astals, Sergi; Villa-Gómez, Denys K.
Abstract: Biological sulfate reduction is an established method leading to new biotechnologies in wastewater treatment. Batch assays are a powerful tool to support sulfate-reducing bacteria (SRB) research and application; however, their methodology is far from been standardized. The present review critically analyses the experimental conditions used for SRB batch assays in literature, to propose a general experimental framework supporting a future standardized protocol. Batch assays using SRB biomass (SRB-test) were grouped in three different categories depending on their objective: (1) test assessing activity of a SRB culture, (2) test determining the reduction potential of an electron donor, and (3) test determining the feasibility of using different sulfate sources as electron acceptor. Considering the methodologies and results from the reviewed publications, set-up and monitoring conditions are recommended to enhance SRB-tests comparability and reproducibility. The recommendations include the use of lactate as electron donor and sodium sulfate as electron acceptor as controls in the SRB-tests. Finally, due to the difficulty to standardize the biomass source, the microbial characterization of the biomass is recommended.